Reconciling the role of serotonin in behavioral inhibition and aversion: acute tryptophan depletion abolishes punishment-induced inhibition in humans. - Crockett, M; Clark, L; Robbins, T (2009)
The neuromodulator serotonin has been implicated in a large number of affective and executive functions, but its precise contribution to motivation remains unclear. One influential hypothesis has implicated serotonin in aversive processing; another has proposed a more general role for serotonin in behavioral inhibition. Because behavioral inhibition is a prepotent reaction to aversive outcomes, it has been a challenge to reconcile these two accounts. Here, we show that serotonin is critical for punishment-induced inhibition but not overall motor response inhibition or reporting aversive outcomes. We used acute tryptophan depletion to temporarily lower brain serotonin in healthy human volunteers as they completed a novel task designed to obtain separate measures of motor response inhibition, punishment-induced inhibition, and sensitivity to aversive outcomes. After a placebo treatment, participants were slower to respond under punishment conditions compared with reward conditions. Tryptophan depletion abolished this punishment-induced inhibition without affecting overall motor response inhibition or the ability to adjust response bias in line with punishment contingencies. The magnitude of reduction in punishment-induced inhibition depended on the degree to which tryptophan depletion reduced plasma tryptophan levels. These findings extend and clarify previous research on the role of serotonin in aversive processing and behavioral inhibition and fit with current theorizing on the involvement of serotonin in predicting aversive outcomes.